Maiden application of rank correlation coefficient for line outage detection using current phasor of PMUs. (2nd September 2020) - Alam, Mehebub; Kundu, Shubhrajyoti; Thakur, Siddhartha Sankar; Banerjee, Sumit
Abstract: This paper presents a new approach to solve line outage detection (LOD) problem utilizing current phasors obtained from phasor measurement units (PMUs). A new term that is, objective coefficient value (OCV), is introduced utilizing the rank correlation coefficient (RCC) and line outage detection is carried out based on the OCV. Moreover, the effect of bad data (BD) and measurement noises are also considered in the developed mathematical model. Furthermore, it has been proved that the suggested scheme can identify outage of parallel lines (PLs), whereas the existing voltage phasor‐based algorithms fail to do so. Moreover, a new logical index that is, performance improvement w.r.t detection accuracy (PIDA) is introduced to quantify the superiority of the proposed scheme over some existing techniques. The developed algorithm is implemented on IEEE 5‐bus, 14‐bus, 57‐bus, 118‐bus systems, and large‐scale Polish 2383‐bus system. The comparison of test results with some existing methods proves the applicability and brevity of the developed algorithm. Abstract : Rank correlation coefficient‐based methodology is presented in this study for the detection of line outage using optimally placed PMUs. The current phasors of PMU are utilized instead of voltage phasors. The methodology is based on comparison of measured line currents with simulated line currents for various outage cases. The impact of measurement noises and bad data is also examined.